Esther Williams. Volume 1 [videorecording (DVD)] - Williams, Esther, 1921-2013; Rathbone, Basil, 1892-1967; Johnson, Van, 1916-2008; Ball, Lucille, 1911-1989; Wynn, Keenan, 1916-1986; Montalbán, Ricardo; Durante, Jimmy, 1893-1980; Lamas, Fernando (Turner classic movies. TCM spotlight., 1944)
Disc 1. "Bathing beauty" - 1944 .; Disc 2. "Easy to wed" - 1946 .; Disc 3. "On an island with you" - 1948 ; Disc 4. "Neptune's daughter) - 1949 Disc 5. "Dangerous when wet" - 1953.